Dialog Komunitas: Menggabungkan Teknologi dan Metodologi Mengajar Inovatif di Sekolah - Gani, Ahmad; Hidayat, Taufik (Jurnal Pengabdian Masyarakat Sultan Indonesia, 2024)
Integrating technology into the education process is an important step towards the digital age, especially in Jakarta's school environment. "Community Dialogue: Combining Technology and Innovative Teaching Methodologies in Schools" started as a discussion forum aimed at addressing issues and opportunities related to the application of technology in education. The event brought together various stakeholders, including teachers, technology experts and policy makers, to share knowledge and best practices with a focus on implementing innovative teaching methodologies. Participants were invited to work together and help build strategies for using technology in the classroom through group discussions and Q&A sessions. Adaptive curriculum development, the use of digital tools in teaching, and blended learning approaches were some of the topics discussed. The results of the discussion showed that teachers should be trained in educational technology and the curriculum should be adapted to support digital learning. As an effort to improve the quality of education in Jakarta, this discussion emphasized the importance of the involvement of all parties in the effective implementation of educational technology. This dedication is very important, especially in providing direction and guidance for schools in Jakarta to use educational technology that is sophisticated and relevant to the needs of students in the modern era.